Why is the philosophy of space important for the vision of sustainable urban development? - Ahmadin (Jurnal Ekonomi dan Riset Pembangunan, 2026)
This article examines the philosophy of space in the epistemological and normative context of its relationship to sustainable urban development. This is crucial amidst the strong influence of the technocratic paradigm in the urban planning process, which tends to reduce space to a physical-economic entity and ignores the social, cultural, and political dimensions. This study uses a qualitative approach based on critical literature studies on relevant topics and theoretical analysis as conceptual legitimacy, with the unit of analysis being the conception of space as a social construction produced through power relations, representational practices, and lived space experiences. The findings of this study indicate that the use of the philosophy of space in urban development offers the opportunity to reorient spatial policies with an inclusive, participatory, and equitable vision. In this context, a reconstruction of the urban development paradigm is needed that places humans, spatial justice, and ecological sustainability as the essence of planning.